Visual Influence on Auditory Perception of Vowels by French-Speaking Children and Adults - Trudeau-Fisette, Paméla; Arnaud, Laureline; Ménard, Lucie (Frontiers in Psychology, 2022)
Audiovisual interaction in speech perception is well defined in adults. Despite the large body of evidence suggesting that children are also sensitive to visual input, very few empirical studies have been conducted. To further investigate whether visual inputs influence auditory perception of phonemes in preschoolers in the same way as in adults, we conducted an audiovisual identification test. The auditory stimuli (/e/-/ø/ continuum) were either presented in an auditory condition only or simultaneously with a visual presentation of the articulation of the vowel /e/ or /ø/. The results suggest that, although all participants demonstrated visual influence on auditory perception, substantial individual differences exist in the 5- to 6-year-old group. While additional work is required to confirm this hypothesis, we suggest that auditory and visual systems are developing at around that age, and that multisensory phonological categorization of the rounding contrast took place only in children whose sensory systems and sensorimotor representations were mature.